A Virtual Platform to Solve Baghdad’s Traffics Jam Based on IoT - Basheer, Hana S. (Al-Nahrain Journal for Engineering Sciences, 2025)
In Urban cities, services are supported by intelligent applications and are connected to each other through ad hoc networks. Any service can be operated using a compatible of an Internet of Things (IoT) technology. This study focuses on the transportation service and finding a non-cost solution to solve the crossroads congestion that affected people time and money. The Wireless Sensor Networks (WSNs) that are planted on the roads can help in monitoring the roads situation by collecting their data and send them through wireless communication to a traffic management center. In this work two phases of time are considered for a crowded area. Low-cost components are suggested to solve the congestion at the cross roads without the need for reconstruct the roads. IoT device such as smart phone can be wirelessly connected to the Traffic Management Center (TMC), which can analyze the incoming data from WSN and send back the calculated time to the police officer to control the green light long and overcome the standard time installed for all directions. The main idea is to solve the congestion problem in real time by extending the time long of the green traffic light for the road direction with the highest vehicle density. The suggested algorithm was operated on a dataset of 6 days and for the time phase from 7:00-10:00am.